2022
DOI: 10.3389/fcimb.2022.805964
|View full text |Cite
|
Sign up to set email alerts
|

Potential Advances of Adjunctive Hyperbaric Oxygen Therapy in Infective Endocarditis

Abstract: Patients with infective endocarditis (IE) form a heterogeneous group by age, co-morbidities and severity ranging from stable patients to patients with life-threatening complications with need for intensive care. A large proportion need surgical intervention. In-hospital mortality is 15-20%. The concept of using hyperbaric oxygen therapy (HBOT) in other severe bacterial infections has been used for many decades supported by various preclinical and clinical studies. However, the availability and capacity of HBOT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 122 publications
(140 reference statements)
0
7
0
Order By: Relevance
“…In the case of clostridial infections, there is persuasive evidence that hyperbaric oxygen therapy at sufficiently high partial pressures halts the production of alpha-toxin, buying precious time for antibiotics to take effect [ 17 ]. Modern understanding of host-pathogen interaction has advanced the use of HBOT beyond gas gangrene to various complicated chronic and acute infections [ 18 ]. Tissue hypoxia below 30mmHg impedes granulocyte and macrophage function, a situation commonly seen in NSTI as infection progresses [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of clostridial infections, there is persuasive evidence that hyperbaric oxygen therapy at sufficiently high partial pressures halts the production of alpha-toxin, buying precious time for antibiotics to take effect [ 17 ]. Modern understanding of host-pathogen interaction has advanced the use of HBOT beyond gas gangrene to various complicated chronic and acute infections [ 18 ]. Tissue hypoxia below 30mmHg impedes granulocyte and macrophage function, a situation commonly seen in NSTI as infection progresses [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data using the present guidelines for the antibiotic treatment of IE indicate the need for improved treatment strategies. HBOT is a promising candidate as an adjunctive treatment strategy due to the multifaceted effects and the pathophysiology of IE (Lerche et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has therefore been advocated that further studies should evaluate ticagrelor for prophylactic treatment of IE in patients with prosthetic valves or indwelling devices [75 ▪ ]. Experimental studies also reported improved outcomes in terms of vegetation size, bacterial load and inflammation reduction with the use of dabigatran, a direct thrombin inhibitor [78 ▪ ]. However, such treatments in are challenging in ICU patients, as they were associated with a major risk of bleeding [75 ▪ ].…”
Section: Managementmentioning
confidence: 99%
“…Hyperbaric oxygen therapy could also be an adjunctive treatment worth exploring in patients with IE. In experimental models of IE, hyperbaric oxygen therapy has been shown to enhance the bactericidal effect of antibiotics [78 ▪ ].…”
Section: Managementmentioning
confidence: 99%